Generation of sub-nanosecond pulses using peaking capacitor - Madhu Palati; Ritu Agarwal; Archana Sharma; Nagabhushana G.R. (Journal of Electrical Systems and Information Technology, 2017)
This paper discusses the analysis, simulation and design of a peaking circuit comprising of a peaking capacitor, spark gap and load circuit. The peaking circuit is used along with a 200 kV, 20 J Marx generator for generation of sub-nanosecond pulses. A high pressure chamber to accommodate the peaking circuit was designed and fabricated and tested upto a pressure of 70 kg/cm2. Total estimated values of the capacitance and inductance of the peaking circuit are 10 pF and 72 nH respectively. At full charging voltage, the peaking capacitor gets charged to a peak voltage of 394.6 kV in 15 ns. The output switch is closed at this instant. From Analysis & Simulation, the output current & rise time (with a matched load of 85 Ω) are 2.53 kA and 0.62 ns.